Spray-drying processing and characterization of sodium nitrite-aluminium - Lee, Priscilla Li Yi (2013)
Spray drying is adopted for the processing of sodium-nitrite-aluminium to investigate how the process of spray drying forms a structure of fuel and oxidizer via the establishment of microencapsulation. This was proposed to improve the interfacial contact between them for good combustion kinetics and thermal properties. Sodium nitrite serves as an oxidizer by releasing oxygen upon thermal decomposition. Aluminium will act as a fuel, which has been extensively used due to its high enthalpy of heat of 31kJ/g.[1] Two sizes of Aluminium were used to explore how they affect the particle formation and thereby the thermal and kinetic properties. [2nd Award]